2017
DOI: 10.5546/aap.2017.eng.65
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and infection in the newborn infant: Does chlorhexidine play a role in infection prevention?

Abstract: Healthcare-associated infections are a major problem in newborn infants, considering their high morbidity, mortality, and long-term sequelae. In preterm infants, it has been shown that skin and gastrointestinal tract colonization undergoes variations compared to healthy term infants, and that preterm infants are more exposed to nosocomial microorganisms given their higher probability of being admitted to the neonatal intensive care unit where they are cared for. This document reviews normal colonization, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…It is used as an antiseptic for medical and veterinarian antisepsis, oral disinfection and hand scrubs (Lowbury and Lilly, 1960 ; Holloway et al, 1986 ; Kuruvilla and Kamath, 1998 ; Traor et al, 2000 ; Gomes et al, 2001 ). Chlorhexidine works against gram positive and negative bacteria, fungi and is spore- and mycobacteriostatic (Davies et al, 1954 ; Beeuwkes, 1958 ; Ortegón et al, 2017 ).…”
Section: Disinfectants and Antiseptics And Their Mechanism Of Actionmentioning
confidence: 99%
“…It is used as an antiseptic for medical and veterinarian antisepsis, oral disinfection and hand scrubs (Lowbury and Lilly, 1960 ; Holloway et al, 1986 ; Kuruvilla and Kamath, 1998 ; Traor et al, 2000 ; Gomes et al, 2001 ). Chlorhexidine works against gram positive and negative bacteria, fungi and is spore- and mycobacteriostatic (Davies et al, 1954 ; Beeuwkes, 1958 ; Ortegón et al, 2017 ).…”
Section: Disinfectants and Antiseptics And Their Mechanism Of Actionmentioning
confidence: 99%
“…A survey of 29 European countries showed that the prevalence of HAIs in NICUs (10.7%) and neonatology wards (3.5%) was unacceptably high 2. HAIs have a significant impact on neonatal morbidity, mortality and long-term sequelae and increase the cost of healthcare 3. Bacterial infections are the main cause of 2.9 million neonatal deaths each year 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…Several practices such as isolation of infected patient, expansion of compliance with hand hygiene, increased environmental cleanliness, and efficient catheter maintenance have been demonstrated to reduce HAIs in NICUs [11]. However, HAIs are still major problem among preterm infants in NICU.…”
Section: Introductionmentioning
confidence: 99%